An oncogenic fusion product of the phosphatidylinositol 3-kinase p85β subunit and HUMORF8, a putative deubiquitinating enzyme - Janssen, Johannes W. G.; Schleithoff, Lothar; Bartram, Claus R.; Schulz, Ansgar Stephan (Oncogene, 1998)
Peripheral blood cell DNA from a patient with a chronic myeloproliferative disorder was tested in the tumorigenicity assay. Upon tumor induction in nude mice we isolated a human oncogene by means of genomic cloning, exon trap analysis and cDNA cloning. Sequence analysis revealed a fusion product of the p85β subunit of phosphatidylinositol (PI) 3-kinase and HUMORF8, a putative deubiquitinating enzyme, which has been generated during the DNA transfection process. Application of the tumorigenicity assay to various p85β and HUMORF8 cDNA constructs indicated that the recombination of both genes rather than the truncation of one of the fusion partners renders the chimeric protein tumorigenic. Moreover, sequence analysis of human wildtype p85β revealed an alanine for serine substitution at a site important for the regulation of the lipid kinase activity of PI 3-kinase in human p85α. This variation may relate to differences in the mode of signal transduction from both p85 isoforms.